International comparisons of prices, output and productivity - Prasada Rao, D. S.; Salazar-Carrillo, Jorge (Amsterdam ; New York : Elsevier, 1996)
The present volume provides a collection of material on the subject of international comparisons, contributed by scholars from a range of relevant disciplines and geographical backgrounds. The papers in this volume have been classified into two broad groups united by overlapping themes. Part I includes essentially empirical papers intended to provide a clear picture of the different types of international comparisons that have been undertaken by various organizations and individuals. The papers relate to empirical studies of different sectoral and national income aggregates at both regional and global levels. The papers in Part II deal with methodological and analytical issues. Discussion of the appropriateness of various aggregation methods for international comparisons accounts for a major component of this section. The volume provides a set of studies on international comparisons of prices, output and productivity, and will provide a reference source for interested readers.
China : the dollar value of gross domestic product / Robert Michael Field -- An assessment of the United Nations scale of assessments, 1946-1994 / Lawrence H. Officer -- Van Ijzeren's method of international price and volume comparison : an exposition / Bert M. Balk -- Consistency in aggregation principle for multilateral comparisons of purchasing power parities and real products / Salem H. Khamis -- Stochastic approach to international comparisons of prices and real income / E. A. Selvanathan -- Structure of international prices : a production-based approach / Yoshimasa Kurabayashi -- A reconsideration of log-change index numbers for international comparisons / Jorge Salazar-Carrillo -- Regression estimates of per capita GDP based on purchasing power parities / Sultan Ahmad -- The PPP doctrine, long term exchange rates and a new method to estimate real gross domestic products / Elio Lancieri -- Productivity, factor endowments, military expenditures, and national price levels / Jeffrey H. Bergstrand -- International comparison program in the 1980s and 1990s / Zoltan Kenessey -- Latin American comparisons for 1985 / Jorge Salazar-Carrillo -- Intercountry comparisons of agricultural output and productivity, 1970-1990 -- A perspective on international comparisons of capital / Michael Ward -- Comparative price and productivity levels : Korea and the United States, 1963-1990 / Dirk Piht.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Prices; Input-output analysis; Industrial productivity; Competition, International; Business & Economics -- Economics -- Macroeconomics; International economics